Author correction: Necroptosis microenvironment directs lineage commitment in liver cancer - Seehawer, Marco; Heinzmann, Florian; D’Artista, Luana; Harbig, Jule; Roux, Pierre-François; Hoenicke, Lisa; Dang, Hien; Klotz, Sabrina; Robinson, Lucas; Doré, Grégory; Rozenblum, Nir; Kang, Tae-Won; et al. (Nature, 2018)
In this Article, the pCaMIN construct consisted of ‘mouse MYC and mouse NrasG12V’ instead of ‘mouse Myc and human NRASG12V; and the pCAMIA construct consisted of ‘mouse Myc and human AKT1’ instead of ‘mouse Myc and Akt1’ this has been corrected online.
The original article was published on 12 September 2018
Gesehen am 04.09.2019